Factor Analysis оf the Efficiency оf Drilling Lateral Shafts with Horizontal Ending - A. V. Zheludkov; V. F. Mishagina (Наука. Инновации. Технологии)
Introduction. One of the ways to increase oil recovery at the late stages of development of mature fields is the drilling of lateral shafts with horizontal sections. Hard-to-recover residual oil reserves are mainly concentrated in the marginal zones of formations with small oil-saturated thicknesses and low permeability. The article studies the efficiency of drilling lateral horizontal shafts and the resulting additional oil production by multifactor analysis with account of geological heterogeneity and technological features.Materials and research methods. The effectiveness of the results obtained when drilling lateral horizontal shafts depends not only on the choice of a point on the map of the oil reservoir, but also on the structure of the residual hard-to-recover oil reserves and the filtration and reservoir properties of the reservoir. The article presents an analysis of the obtained results of drilled horizontal lateral shafts, the placement of which was worked out with account of the facies conditions of formation and geological heterogeneity.Research results and their discussion. The authors analyzed the operation of lateral horizontal shafts from the moment of their launch, which makes it possible to determine the dependence of the efficiency of their work on the joint or separate operation of the AB1 3 and AB2 layers, taking into account the geological features of sedimentation and differences in filtration and capacitance properties. To select prospective wells for cutting the lateral trunk, groups of facies of continental genesis were identified, with which sand bodies are associated.Conclusion. The dependency of technological parameters of the lateral second shafts on geological features is traced. On the basis of factor analysis directions for further approaches to the drilling of the UW are specified. Monitoring of the actual data determined the factors affecting the efficiency of the input technological indicators of the wells.